2011
DOI: 10.1007/s13580-011-0143-3
|View full text |Cite
|
Sign up to set email alerts
|

Agro-morphological characterization of anther derived plants in sweet pepper (Capsicum annuum L. cv. Boogie)

Abstract: This study was conducted in sweet pepper 'Boogie' to produce the haploids and diploids via anther culture, and to characterize their plant and fruit characters. Anthers were cultured on Dumas de Vaulx medium, (C-medium) supplemented with 0.1 mg L -1 kinetin and 0.1 mg L -1 2, 4-D, and 3% sucrose and 0.32% phytagel. Cultures were first incubated in dark at 35 for one week and then transferred at 25 under 16 h photoperiod for 40 days. Regenerated plantlets including haploids and diploids were evaluated for their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 15 publications
4
11
2
Order By: Relevance
“…Other researchers presented results of leaves dimensions of diploid androgenic plants smaller than the mother genotype which is opposite to our results [24,26].…”
Section: Morphological Traits Of Androgenic Plantscontrasting
confidence: 99%
See 3 more Smart Citations
“…Other researchers presented results of leaves dimensions of diploid androgenic plants smaller than the mother genotype which is opposite to our results [24,26].…”
Section: Morphological Traits Of Androgenic Plantscontrasting
confidence: 99%
“…Based on analysis of diploid populations in comparison to control variety Boogie, they selected some elite diploid lines for development of sweet pepper varieties. Similarly, it was suggested that existing variation within diploid population might be due to the anther culture and it is a naturally produced variation [26]. Variation in plant and fruit characters was observed in anther derived spontaneous diploid population of minipaprika.…”
Section: Morphological Traits Of Fruits From Androgenic Plantsmentioning
confidence: 98%
See 2 more Smart Citations
“…During the past years, in vitro pepper androgenesis research is extended although its successful application depends on different external factors as pepper genotype, stage of microspores development and growth conditions of mother plants [4][5][6]. Still, there are reports on androgenic pepper lines with improved morphological and quality traits [7][8]. The breeding importance of androgenic lines can be determined on the basis of analysis of plant and fruit traits in successive generations.…”
Section: Introductionmentioning
confidence: 99%